Comparative Analysis of Bread Properties Using Germinated and Un-Germinated Chickpea Flour - Gautam, Navin; Subedi, Ashma; Panta, Om Prakash (NPRC Journal of Multidisciplinary Research, 2025)
The aim of this study was to prepare and compare bread from refined wheat flour (RWF), germinated chickpea flour (GCF) and un-germinated chickpea flour (UGCF). The proximate composition of the flours was analyzed, and bread recipes were formulated using Design Expert software. Bread was prepared with varying proportions of refined wheat flour and UGCF. A (RWF: UGCF = 96.8:3.2), B (RWF: UGCF = 93.6:6.4), C (RWF: UGCF = 90.6:9.4), D (RWF: UGCF = 87.2:12.8), E (RWF: UGCF = 81.4:18.6), F (RWF: UGCF = 78.2:21.8), G (RWF: UGCF = 75:25), and H (RWF: UGCF = 100:0). The straight dough method was employed to prepare the bread. All variations showed significant differences (p0.05) were found between bread made with GCF and UGCF regarding ash content, carbohydrate, iron, and calcium. Significant differences (p